Aspek Keperdataan dalam Upaya Penyelesaian Sengketa Medis antara Pasien dengan Tenaga Medis Berdasarkan Undang-Undang Kesehatan - Camellia, Lintang Zandra; Kartika, Adhitya Widya (Jurnal Hukum & Pembangunan, 2024)
Medical disputes in the civil field are disputes that can occur between patients and doctor as a medical-professionals and are related to the full fillment of the rights and obligations of the binding relationship as a legal result in the provision of medical services. Medical disputes can lead to losses suffered by patients which can be in the form of limb disability, even death. The emergence of law and health provides a beneficial collaboration, where the health field can be used to face public health challenges and the law can be used to maintain peace and order in society. The regulation of health law in Indonesia contained in Law No. 36 of 2009 which has now been amended by Law No. 17 of 2023 provides differences in efforts to resolve medical disputes which are important to examine and are the focus of this research. The author's research was conducted using a juridical-normative legal methodology with a conceptual approach and a statutory approach. The civil aspect in the settlement of medical disputes is that there are losses suffered by patients due to negligence committed by medical personnel. Patients have the right to claim compensation which can be done by litigation or non-litigation. The parties involved in medical dispute resolution want a dispute resolution that is closed and provides a sense of security, especially on the part of medical personnel so that their reputation is not tainted, so they prefer to conduct non-litigation dispute resolution. Law No. 17 of 2023 provides several options for dispute resolution using Alternative Dispute Resolution which in Law No. 36 of 2009 medical dispute resolution can only be done by mediation.